Low Birth Weight among Deliveries, and Adolescent and Advanced Maternal Age Pregnancy - Yadav, Gopal Kumar; Paudel, Binod; Chaudhary, Arjun Prasad; Mahato, Gaurav; Pyakurel, Prajjwal (Journal of Nepal Health Research Council, 2023)
Background: We did this study to evaluate the prevalence of low birth weight among deliveries, adolescent pregnancy and advanced maternal age pregnancy. We also assessed the factors affecting the low birth weight among institutional deliveries at the level of primary hospital.Methods: A hospital-based retrospective cross-sectional study was done in Grahun Primary Hospital of Syangja, Nepal using data maintained in register book over last five years. We excluded all those deliveries with multiple pregnancy and incomplete records, and included 2473 participants in final analysis using convenient sampling. The relevant information was filled up in Microsoft Excel 2019 v16.0 and descriptive and inferential statistics was calculated using statistical package for social sciences, IBM SPSS® v21 (IBM, Armonk, New York).Results: The prevalence of low birth weight at Grahun Primary Hospital was 11.08%. The prevalence of adolescent pregnancy and advanced maternal age pregnancy was 18.03% and 02.18% respectively. Male newborns had significantly higher mean birth weight as compared to the female newborns (3101.48 ± 506.60 v/s 2967.53 ± 484.97, P-value <0.001). Female newborns had higher odds of low birth weight as compared to those male newborns (11.99% v/s 8.29%, AOR=1.56, 95% CI= 1.17-2.07). Pregnant women with lower gestational age (<37 weeks or preterm) had a higher odds of low birth weight as compared to pregnant women with normal gestational age (37-42 weeks) (AOR = 11.59, 95% CI 8.49-15.83).Conclusions: The low birth weight depends upon gestational age of mother and gender of newborn. Local organizations should work to bring down low birth weight, and adolescent pregnancy and advanced maternal age pregnancy of mother.Keywords: Low birth weight; Nepal; primary hospital; teenage/adolescent pregnancy.